Theoretical Study of the Chemical Properties and the Reaction Pathway of Decarbonylative Alkylative Esterification of Styrenes with Aliphatic Aldehydes - Meysam Madahi; Dadkhoda Ghazanfari; Sayed Ali Ahmadi (Journal of Chemistry)
Using inexpensive and available aliphatic aldehydes as an alkyl source is a useful and cost-effective way to extend the chain of benzyl esters; this decarbonylative alkylative esterification of styrene derivatives has been used for organic synthesis and medical chemistry. A cocatalyzed decarbonylative alkylative esterification of styrene derivatives with aliphatic aldehydes and iodobenzenediacetate to provide chain elongated benzoates was investigated by the density functional theory, and quantum theory of atoms in molecules analysis has been used. The chemical properties and the reaction pathway between styrene and aldehyde derivatives in the presence of PhI(OAc)2 and Co(OAc)2 have been studied. Chemical properties of styrene and aldehyde derivatives for detecting the stability of products were studied using HOMO and LUMO, potential electronic chemical, global hardness, and global electrophilicity power. The molecular electron potential results show that the styrene and its derivatives are electron donors and aldehyde derivatives are electron acceptors. The localized orbital locator, electron location function analysis, and quantum theory of atoms in the molecule have been used to study the active sites for interactions between reactants. The decarbonylative alkylative esterification was restricted exclusively to cobalt catalysts. The step of ligand exchange was the rate-determining step for this reaction.